Quantifying the impact of grain for green program on ecosystem service management: a case study of Exibei region, China - Yu, Qianru; Feng, Chen-Chieh; Xu, NuanYin; Guo, Luo; Wang, Dan (MDPI, 2019)
Evaluating the impact of an ecological restoration program on ecosystem services is crucial, given the role of such a program in boosting sustainable ecosystem management. This study examines the impact of one of the large-scale ecological restoration programs in China, the Grain for Green Program (GGP), on ecosystem service management in the Exibei region of China. This region is studied, as it is a key source water area with rich biodiversity and has been experiencing GGP for 20 years. To achieve the stated goal the changes of land use and ecosystem services value (ESV) and the ecosystem services scarcity value (ESSV) in the Exibei region were quantified and assessed based on remote sensing images from 1990, 1995, 2000, 2005, 2010, 2015 and field survey data. The results indicated that the expansion of construction land and the increase of water body were the dominant land use changes throughout the study period. Farmland, forestland and grassland decreased by 2.61%, 0.47% and 1.41% after the GGP, respectively. The ESV of the entire Exibei region increased slightly in response to land use change during 1990-2015, with an annual loss of 0.08% before the implementation of GGP and an annual growth of 0.03% after the implementation of GGP. Moreover, forestland was the dominant contributor to ESSV after the implementation of the GGP. Its annual growth rate was four times higher than before the commencement of GGP. The results of this study contribute to the protection of the Exibei region ecosystem, and more importantly, the future management of the ecosystem service in the hilly regions of southern China.